The Role of Zakat and Waqf Institutions in addressing Sustainable Water Management and Security Challenges among the Organization of Islamic Cooperation Countries - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Shafa’at Ahmad Aliyu; Adama Lawal Tafida (Research Synergy Foundation, 2024)
Significant issues with water management and security face the countries of the Organization of Islamic Cooperation (OIC); these challenges are worsened by pressures from economic expansion, population growth, and climate change. Islamic financial instruments such as Zakat and Waqf provide creative means of addressing these issues. This paper examines the possible effects of Zakat and Waqf on sustainable water management and security solutions in the Organization of Islamic Cooperation (OIC) countries, emphasizing their historical relevance, current uses, and potential future developments. A multidisciplinary method was used to conduct a thorough analysis, incorporating viewpoints from Islamic finance, environmental science, and public policy. A qualitative research method was used through literature review, and interview with about twelve (12) pertinent people from six (6) categories of people to gather data. The conclusions of this research imply that Zakat and Waqf have a great deal of potential to support OIC nations’ sustainable water management and security. The study concludes with actionable suggestions for governments, NGOs, policymakers, and community leaders with the goal of maximizing the application of Zakat and Waqf to resolve water-related issues. In order to accomplish sustainable development goals, this research emphasizes how crucial it is to include traditional Islamic financial tools into contemporary water management systems.